ENTREPRENEURSHIP BEGINS IN MAKHALLAS (Scientific journal of the Fergana State University, 2023)
The development of entrepreneurship and national economics on the basis of the market relations is one of the leading policies of the state. The given article touches upon the issues of the development of the entrepreneurship in makhallas. In the result of it, the unemployed support and minor business development are in future perspectives.